Is pre‐referral management of anterior urethral strictures prior to urethroplasty appropriate?. (30th December 2020) - Ojima, Kenichiro; Horiguchi, Akio; Shinchi, Masayuki; Hirano, Yusuke; Hamamoto, Koetsu; Kimura, Fumihiro; Takahashi, Eiji; Asano, Tomohiko; Ito, Keiichi; Azuma, Ryuichi
Abstract : Objectives: To evaluate whether the management of anterior urethral strictures prior to definitive urethroplasty is appropriate. Methods: Of a total of 419 men diagnosed with anterior urethral strictures at hospitals across Japan and thereafter referred to our institution for definitive urethroplasty between 2004 and 2019, the medical records of 371, for whom data on stricture characteristics at the initial diagnosis and pre‐referral management were available, were retrospectively reviewed. A pre‐referral single transurethral procedure, such as direct vision internal urethrotomy or urethral dilation, was considered appropriate only for favorable stricture, defined as a single nontraumatic untreated bulbar urethral stricture ≤2 cm in size, and repeat transurethral procedures were considered inappropriate in any circumstances. The association between the appropriateness of the pre‐referral management strategy and patient and clinical characteristics was analyzed. Results: A total of 242 patients (65.2%) had a pre‐referral history of at least one transurethral procedure, and performing the procedure was considered inappropriate for 221 patients (59.6%). On multivariate logistic regression analysis, location of the patient's residence far from our institution (outside of the Kanto area; odds ratio 3.35, 95% confidence interval 1.86–6.04; P  < 0.0001), voiding with intermittent dilation (odds ratio 2.38, 95% confidence interval 1.38–4.12; P  = 0.002), iatrogenic stricture (odds ratio 11.18, 95% confidence interval 5.30–23.61; P  < 0.0001), and stricture longer than 20 mm (odds ratio 3.05, 95% confidence interval 1.47–6.38; P  = 0.003) were the independent predictors of inappropriate use of transurethral procedures. Conclusions: Transurethral procedures are often inappropriately used. There is a clear need to promote appropriate management strategies for urethral strictures among general urologists.